The Effect of Glycerin Content in Sodium Alginate/Poly(vinyl alcohol)-Based Hydrogels for Wound Dressing Application - Katarzyna Bialik-Wąs (MDPI AG, 2021)
The impact of different amounts of glycerin, which was used in the system of sodium alginate/poly(vinyl alcohol) (SA/PVA) hydrogel materials on the properties, such as gel fraction, swelling ability, degradation in simulated body fluids, morphological analysis, and elongation tests were presented. The study shows a significant decrease in the gel fraction from 80.5 ± 2.1% to 45.0 ± 1.2% with the increase of glycerin content. The T5 values of the tested hydrogels were varied and range from 88.7 °C to 161.5 °C. The presence of glycerin in the matrices significantly decreased the thermal resistance, which was especially visible by T10 changes (273.9 to 163.5 °C). The degradation tests indicate that most of the tested materials do not degrade throughout the incubation period and maintain a constant ion level after 7-day incubation. The swelling abilities in distilled water and phosphate buffer solution are approximately 200–300%. However, we noticed that these values decrease with the increase in glycerin content. All tested matrices are characterized by the maximum elongation rate at break in a range of 37.6–69.5%. The FT-IR analysis exhibits glycerin changes in hydrogel structures, which is associated with the cross-linking reaction. Additionally, cytotoxicity results indicate good adhesion properties and no toxicity towards normal human dermal fibroblasts.